Antioxidant activity and flavor compounds of hickory yogurt. Issue 8 (3rd August 2017) - Su, Nana; Ren, Li; Ye, Hongling; Sui, Yuan; Li, Jinglei; Ye, Ming
ABSTRACT: Hickory milk and reconstituted milk (about 12 g/100 g total solid) were mixed in the proportion of 3:7 by volume to prepare hickory milk yogurt. Cow milk yogurt was used as control. The acidity and total count of lactic acid bacteria of hickory milk yogurt were not significantly different from cow milk yogurt ( p > 0.05). Compared with cow milk yogurt, hickory milk yogurt had higher total solids, fat, crude protein, and amino acids, but lower ash and not-fat solids. Sensory evaluation showed that the appearance and flavor scores of hickory milk yogurt had no significant difference from cow milk yogurt ( p > 0.05), but the texture score was significantly higher ( p < 0.05). IC50 values in relation to 1, 1-diphenyl-2-picrylhydrazyl scavenging activity and inhibition of lipid peroxidation (46.88 and 26.70 g/L) of hickory milk yogurt were significantly lower than those of cow milk yogurt which suggested that the antioxidant activity of hickory milk yogurt was significantly higher than cow milk yogurt ( p < 0.05). There were 30 and 28 kinds of volatile compounds identified in hickory milk yogurt and cow milk yogurt, respectively. Compared with cow milk yogurt, the concentration of acetaldehyde, hexanal, nonanal, 2-nonanone, caproic acid, heptylic acid, and nonanoic acid in hickory milk yogurt increased significantly, and the concentration of benzaldehyde, 2, 3-pentanedione, 2, 3-butanedione, 3-hydroxy-2-butanone, acetic acid, butyric acid, and benzoic acid decreased significantly ( p < 0.05).